4) ![ctg^{2} \alpha ctg^{2} \beta -\frac{cos^{2}(\alpha -\beta )+cos^{2}(\alpha +\beta )}{2sin^{2}(-\alpha) sin^{2}\beta} = ctg^{2} \alpha ctg^{2} \beta -\frac{cos^{2}\alpha cos^{2}\beta+sin^{2}\alpha sin^{2}\beta +cos^{2}\alpha cos^{2}\beta-sin^{2}\alpha sin^{2}\beta}{2sin^{2}\alpha sin^{2}\beta} =ctg^{2} \alpha ctg^{2} \beta -\frac{2cos^{2}\alpha cos^{2}\beta}{2sin^{2}\alpha sin^{2}\beta} = ctg^{2} \alpha ctg^{2} \beta-ctg^{2} \alpha ctg^{2} \beta = 0 ctg^{2} \alpha ctg^{2} \beta -\frac{cos^{2}(\alpha -\beta )+cos^{2}(\alpha +\beta )}{2sin^{2}(-\alpha) sin^{2}\beta} = ctg^{2} \alpha ctg^{2} \beta -\frac{cos^{2}\alpha cos^{2}\beta+sin^{2}\alpha sin^{2}\beta +cos^{2}\alpha cos^{2}\beta-sin^{2}\alpha sin^{2}\beta}{2sin^{2}\alpha sin^{2}\beta} =ctg^{2} \alpha ctg^{2} \beta -\frac{2cos^{2}\alpha cos^{2}\beta}{2sin^{2}\alpha sin^{2}\beta} = ctg^{2} \alpha ctg^{2} \beta-ctg^{2} \alpha ctg^{2} \beta = 0](https://tex.z-dn.net/?f=+ctg%5E%7B2%7D+%5Calpha++ctg%5E%7B2%7D+%5Cbeta+-%5Cfrac%7Bcos%5E%7B2%7D%28%5Calpha+-%5Cbeta+%29%2Bcos%5E%7B2%7D%28%5Calpha+%2B%5Cbeta+%29%7D%7B2sin%5E%7B2%7D%28-%5Calpha%29+sin%5E%7B2%7D%5Cbeta%7D++%3D+ctg%5E%7B2%7D+%5Calpha++ctg%5E%7B2%7D+%5Cbeta+-%5Cfrac%7Bcos%5E%7B2%7D%5Calpha+cos%5E%7B2%7D%5Cbeta%2Bsin%5E%7B2%7D%5Calpha+sin%5E%7B2%7D%5Cbeta+%2Bcos%5E%7B2%7D%5Calpha+cos%5E%7B2%7D%5Cbeta-sin%5E%7B2%7D%5Calpha+sin%5E%7B2%7D%5Cbeta%7D%7B2sin%5E%7B2%7D%5Calpha+sin%5E%7B2%7D%5Cbeta%7D+%3Dctg%5E%7B2%7D+%5Calpha++ctg%5E%7B2%7D+%5Cbeta+-%5Cfrac%7B2cos%5E%7B2%7D%5Calpha+cos%5E%7B2%7D%5Cbeta%7D%7B2sin%5E%7B2%7D%5Calpha+sin%5E%7B2%7D%5Cbeta%7D+%3D+ctg%5E%7B2%7D+%5Calpha++ctg%5E%7B2%7D+%5Cbeta-ctg%5E%7B2%7D+%5Calpha++ctg%5E%7B2%7D+%5Cbeta+%3D+0+)
5) sinα - cosα = √2/2; (sinα - cosα)² = (√2/2)²; cos²α - 2cosαsinα + sin²α = 1/2;
1 - 2cosαsinα = 1/2; cosαsinα = 1/4
cos³α - sin³α = ( cosα - sinα)( cos²α + cosαsinα + sin²α) = ( cosα - sinα)( 1 + cosαsinα) = -√2/2(1 + 1/4) = -√2/2 · 5/4 = (-5√2)/8.